Insights into the charge storage mechanism of binder-free electrochemical capacitors in ionic liquid electrolytes - Pal, Bhupender; Parameswaran, Abhilash Karuthedath; Wu, Bing; Děkanovský, Lukáš; Mazánek, Vlastimil; Sarkar, Kalyan Jyoti; Jose, Rajan; Sofer, Zdeněk (American Chemical Society (ACS Publications), 2023)
Electrochemical capacitors (synonymously supercapacitors) working under an electrochemical double-layer charge storage mechanism (EDLC) are widely investigated because of their excellent power density and cycle life; however, their energy density is lower than those of lithium-ion batteries. Ionic liquids (ILs) are of great interest as electrolytes for EDLCs due to their wide operational voltage window. Here, we provide a systematic investigation on the influence of anions of ILs on the charge storage mechanism and electrochemical stability of EDLC electrodes. Two IL electrolytes, viz., [1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI)], having similar cations but different anions and carbon nanotube (CNT) electrodes are chosen for this study. The CNT//BF4:TFSI//CNT-based device showed superior electrochemical performance (∼69 F•g-1 gravimetric specific capacitance, ∼949 W•kg-1 power density, and ∼139 Wh•kg-1 energy density at 0.5 A•g-1) to CNT//EMIMBF4//CNT and CNT//EMIMTFSI//CNT devices. The device using a mixture of BF4:TFSI (1:0.5) electrolytes has an operating voltage of 0-3.8 V and specific capacitance retention of ∼45% at 0.5 A•g-1 after 500 cycles. In the case of the IL mixture (BF4:TFSI), the combined anion structure and their properties play very crucial part in the improvement of the electrochemical performance of the CNT//BF4:TFSI//CNT device. The assembled Teflon Swagelok-type cell could light up green (3.3 V) and red (2.1 V) light-emitting diodes for more than 5 min.